2019
DOI: 10.1111/apt.15221
|View full text |Cite
|
Sign up to set email alerts
|

Editorial: diastolic dysfunction seems not to be decisive for survival after transjugular intrahepatic portosystemic stent‐shunt

Abstract: Linked ContentThis article is linked to Armstrong et al paper. To view this article, visit https://doi.org/10.1111/apt.15164.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
1
1
1
Order By: Relevance
“…Data from this study confirm the higher frequency of LVDD in decompensated cirrhotics, particularly in patients with advanced hemodynamic changes, HRS and refractory ascites, in agreement with a recent systematic review [27]. However, LVDD is not an absolute contraindication to TIPS, particularly in grade 1 and normal systolic function, but requires particular attention and care, especially in subjects with more advanced grades [22,28]. In the setting of TIPS for refractory ascites, these observations support the use of a TDI assessment with a complete morphological evaluation for better select patients in regard to the risk of poor clinical response and cardiac decompensation.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Data from this study confirm the higher frequency of LVDD in decompensated cirrhotics, particularly in patients with advanced hemodynamic changes, HRS and refractory ascites, in agreement with a recent systematic review [27]. However, LVDD is not an absolute contraindication to TIPS, particularly in grade 1 and normal systolic function, but requires particular attention and care, especially in subjects with more advanced grades [22,28]. In the setting of TIPS for refractory ascites, these observations support the use of a TDI assessment with a complete morphological evaluation for better select patients in regard to the risk of poor clinical response and cardiac decompensation.…”
Section: Discussionsupporting
confidence: 90%
“…For these reasons, the diastolic dysfunction should be evaluated by early diastolic peak velocity of mitral annulus (E′) measurement by TDI [12,16]. Previous studies showed a low clinical significance of cardiac abnormalities and a low impact of cardiac dysfunction on medium-term prognosis in patients with cirrhosis but small populations were analysed, LVDD severity was not evaluated and invasive haemodynamic studies were not performed [20][21][22]. In our study, NR to TIPS was associated not only with LVDD, but frequently with its advanced stages (grades 2-3) and with the presence of worse baseline indices, such as left atrial dilation and increase of LVEDV.…”
Section: Discussionmentioning
confidence: 99%
“…Armstrong et al examined a large cohort of 117 patients but none of the echocardiography measures pre-intervention were related to 30-day or overall transplant-free survival after TIPS insertion. Hence, there are no reliable parameters in echocardiography to predict outcome and overall survival in these patients (11,12). In the present study, we found no correlation between TTE parameters before and after TIPS insertion with survival.…”
Section: Discussioncontrasting
confidence: 72%